Under Armour : creating and growing a new consumer brand - Sternthal, Brian; Malaviya, Prashant (London : Kellogg School of Management, 2018)
The case traces the development of the Under Armour (UA) brand, product, and market growth under CEO and founder Kevin Plank from its inception in 1996 through 2016. UA provides a cohesive case study of how to launch and sustain a consumer brand even in the face of its third-party manufacturing approach, which gives its apparel no patentable design or fabric technologies. The case uses UA's brand and advertising development as a backdrop for the current pivotal issue of how to target women to sustain growth. Under Armour's stated goal is to build a $1.9 billion women's business by 2019.
Originally Published InSternthal, B., & Malaviya, P. (2018). Under Armour: Creating and Growing a New Consumer Brand. 5-316-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Under Armour (Firm) -- Case studies; Clothing and dress -- Marketing -- Case studies; Branding (Marketing) -- Case studies